Reconstruction of the Digital Asset Execution Mechanism in the Indonesian Civil Law Framework - Mansur, Moch; Mangar, Irma; Saputra, Toni Eka (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
The development of digital assets as a new form of wealth poses serious challenges to Indonesian civil law, especially in terms of recognition and enforcement mechanisms. This study aims to analyze the extent to which Indonesia's civil law is currently able to accommodate the existence of digital assets and formulate a reconstruction of the ideal execution mechanism to ensure legal certainty and effectiveness in the implementation of court decisions. The research method used is normative legal research with a legislative and conceptual approach, through literature studies on primary, secondary, and tertiary legal materials. The results of the study show that Indonesia's civil law still faces conceptual and normative limitations in qualifying digital assets as legal objects, and does not yet have an execution mechanism that is adaptive to the characteristics of digital assets that are technology-based, intangible, and cross-jurisdictional. The existing execution mechanism is still oriented towards physical mastery, so it is not effective in reaching digital assets based on access control and cryptography. Therefore, a comprehensive legal reconstruction is needed, including affirming the legal status of digital assets as a civil law object with special characteristics, the development of an execution mechanism based on access control, the involvement of third parties (intermediaries), as well as the use of technology and strengthening cross-jurisdictional cooperation. This reconstruction is expected to create an adaptive legal system, provide legal certainty, and ensure the effectiveness of the implementation of court decisions in the digital era.